Integrating Minahasa Folklore Values Through Digital Media in Indonesian Language Learning: A Case Study at SMK Negeri 1 Tombariri - Margareth Winokan; Santje Iroth; Grace S.Luntungan (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study investigates the integration of Minahasa cultural values through digital media in Indonesian language learning at SMK Negeri 1 Tombariri. Employing a qualitative descriptive approach, the research focuses on the use of Canva digital posters in teaching the folklore "Kekekow Bird and Poor Girl" to tenth-grade students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that integrating Minahasa folklore with Canva effectively facilitates students' understanding and visualization of cultural values such as honesty, hard work, gratitude, and social solidarity (Mapalus). Students demonstrated improved reading, writing, and speaking skills, alongside enhanced creativity and digital literacy. The media's visual and interactive nature made learning more engaging and contextual, fostering a deeper appreciation for local culture. This study concludes that Canva is an effective pedagogical tool for transmitting cultural heritage and developing 21st-century competencies in language education.